2011
DOI: 10.1371/journal.pone.0027042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hepatic Niche Harboring Human Acute Lymphoblastic Leukemic Cells via the SDF-1/CXCR4 Axis

Abstract: In acute lymphoblastic leukemia (ALL) patients, the bone marrow niche is widely known to be an important element of treatment response and relapse. Furthermore, a characteristic liver pathology observed in ALL patients implies that the hepatic microenvironment provides an extramedullary niche for leukemic cells. However, it remains unclear whether the liver actually provides a specific niche. The mechanism underlying this pathology is also poorly understood. Here, to answer these questions, we reconstituted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 41 publications
(61 reference statements)
3
32
0
Order By: Relevance
“…2 We confirmed BM engraftment in recipients by flow cytometry, and using both histological and radiological techniques, we could demonstrate that they had patterns of CNS involvement mimicking those seen in patients with CNS disease (supplemental Figures 1 and 2). B-ALL cells have an inherent capacity to infiltrate the CNS, 3 and we observed that by 6 months, recipient mice had CNS disease, regardless of whether the patients whose leukemic cells they received had CNS disease at the time the cells were donated for research.…”
supporting
confidence: 62%
“…2 We confirmed BM engraftment in recipients by flow cytometry, and using both histological and radiological techniques, we could demonstrate that they had patterns of CNS involvement mimicking those seen in patients with CNS disease (supplemental Figures 1 and 2). B-ALL cells have an inherent capacity to infiltrate the CNS, 3 and we observed that by 6 months, recipient mice had CNS disease, regardless of whether the patients whose leukemic cells they received had CNS disease at the time the cells were donated for research.…”
supporting
confidence: 62%
“…27; Central Institute of Experimental Animals, Kawasaki, Japan) were transplanted with SU-Ph2 or SU/SR cells (1 Â 10 6 cells) through the tail vein without preconditioning. Three weeks after transplantation, when engraftment of leukemia cells was confirmed in bone marrow, imatinib (400 mg/kg/dose) or PD0332991 (150 mg/kg/dose) dissolved in deionized water or deionized water as the vehicle was orally administered through a gastric tube.…”
Section: Xenograft Modelmentioning
confidence: 99%
“…26 In brief, PB mononuclear cells (PBMCs) obtained from TAM patients (1-3 3 10 6 cells) were injected into 2.4 Gy-irradiated 8-to 12-week-old NOG mice through the tail vein. To screen for the proliferation of TAM-derived cells, bone marrow (BM) cells were aspirated from the tibia every 4 weeks.…”
Section: Primary and Serial Xenogeneic Transplantation Into Nog Micementioning
confidence: 99%
“…We previously described the development of novel immunodeficient NOD/Shi-scid, interleukin (IL)-2Rg null (NOG) mice with a superior capacity for the engraftment of human hematopoietic and neoplastic cells. [23][24][25][26] In contrast to a previous study in which TAM cells showed a limited ability to expand in immunodeficient mice, 27 we established a xenograft model where TAM cells were transplanted into NOG mice to recapitulate the pathophysiology of TAM/ ML-DS. This xenograft model in combination with high-throughput genomic technology was used to show that genetically heterogeneous minor subclones with leukemia-initiating potential already exist in the neonatal TAM phase and could serve as initiating clones evolving to ML-DS in a patient.…”
Section: Introductionmentioning
confidence: 99%